Development of Integrated Assessment Instrument to Measure Critical Thinking Skills and Self-Efficiency in Acid-Base Concept - Nuryuliana Nuryuliana; Anti Kolonial Prodjosantoso (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research is to describe the stages of developing and validating a product which includes content validity and constructs validity. The method used is Research and Development (R&D) with define, design, develop, and disseminate (4D) model. The initial product was validated by material and learning evaluation expert lecturer. The suitability of the items evaluated by chemistry teacher based on indicators of competency achievement. The sample selection was determined by stratified random sampling of 170 students of 11th grade senior high school in Yogyakarta City. Content validity was analyzed using Aiken's V formula. The results of data analysis show that all components of the test instrument are valid with Aiken's V value greater than 0.80 with a significance of 0.05. Verification of construct validity was analyzed using exploratory factor analysis with the help of the SPSS version 21.0 program. The results prove that all components in the integrated assessment instrument are suitable to be used to measure the critical thinking skills and self-efficacy of students on acid-base concept.